무선 센서 네트워크에서 헥사곤 모델에 기반한 효율적인 비콘 스케줄링 기법 - 이택균 (한국컴퓨터정보학회논문지, 2018)
In this paper, we propose a hexagon model-based efficient beacon frame scheduling approach for wireless sensor networks. The existing beacon frame scheduling approaches use a lot of slots and subslots for the beacon frame scheduling. Thus, the data from source nodes are not efficiently delivered to a sink node. Also in case a sink node needs to broadcast a beacon frame to the nodes in the network, delivering the beacon frame to the network nodes is not efficient as well. Thus, to solve the problem, we use a hexagon model to find the number of slots and subslots for the beacon frame scheduling. By using them for the beacon frame scheduling, the proposed approach performs better than other approaches in terms of the data transmission delay, the number of received data, the beacon transmission delay and the number of relaying the beacon frames.
Keywords: Beacon; Scheduling; Slot; Collision; Cluster Tree; Wireless Sensor Networks